2020
DOI: 10.1002/pol.20200557
|View full text |Cite
|
Sign up to set email alerts
|

Understanding interactions between poly(styrene‐co‐sodium styrene sulfonate) and single‐walled carbon nanotubes

Abstract: Understanding formation mechanisms of hybrids of carbon nanotubes (CNTs) wrapped by polymers and their interactions is critical in modifying solubility of CNTs in aqueous solution and developing new nanotube‐based polymer materials. In the present work, we investigate the structural details of poly(styrene‐co‐sodium styrene sulfonate) (PSS) wrapping around the CNT and the interactions between the PSS chain and the CNT using molecular dynamics (MD) simulations. The fraction of sulfonated groups significantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 61 publications
(111 reference statements)
0
8
0
Order By: Relevance
“…That is supported by the facts that D 2 O has much larger dielectric constant than polymers (D 2 O: 78; PVA: 7; , PVP: ∼4; PAA: 6; PSS (a partly sulfonated form): ∼20). Loose polymer wrapping can be attributed to electrostatic repulsion between the negatively charged PAA and PSS side chains of carboxylate and sulfonate groups, respectively. , Li et al reported that the PSS benzene­sulfonate groups were mostly arranged radiating outward from the SWCNT surface to interact with water molecules in their MD simulations, suggesting that a direct interaction between the hydrophilic polymer side chains and the SWCNT surface would be a minor contributor for the observed peak shifts in our experiments . In addition, they reported that increasing the number of the PSS units in the polystyrene copolymers induced looser wrapping of the SWCNT surfaces due to electrostatic repulsion of the side chains.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…That is supported by the facts that D 2 O has much larger dielectric constant than polymers (D 2 O: 78; PVA: 7; , PVP: ∼4; PAA: 6; PSS (a partly sulfonated form): ∼20). Loose polymer wrapping can be attributed to electrostatic repulsion between the negatively charged PAA and PSS side chains of carboxylate and sulfonate groups, respectively. , Li et al reported that the PSS benzene­sulfonate groups were mostly arranged radiating outward from the SWCNT surface to interact with water molecules in their MD simulations, suggesting that a direct interaction between the hydrophilic polymer side chains and the SWCNT surface would be a minor contributor for the observed peak shifts in our experiments . In addition, they reported that increasing the number of the PSS units in the polystyrene copolymers induced looser wrapping of the SWCNT surfaces due to electrostatic repulsion of the side chains.…”
Section: Resultsmentioning
confidence: 59%
“…19 Although such interesting phenomena have been observed, a deeper understanding of polymer-wrapped SWCNTs at the molecular level is necessary to elucidate the mechanism leading to the interesting phenomena and to facilitate the design of custom functionalities. 20,21 As a characteristic of the individualized semiconducting SWCNTs, PL in the near-infrared (NIR) region (800−2500 nm) is observed. 8 Recently, locally functionalized SWCNTs (lf-SWCNTs), synthesized by slight amount of chemical functionalization of SWCNTs, have been reported to emit red-shifted and brighter defect PL (E 11 * PL) compared to native PL from pristine SWCNTs based on the lowest energy transition (E 11 transition).…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, addition of a large amount of thermal fillers is required to achieve a satisfied TC of composites, but the mechanical properties of thermosets will be deteriorated. Among them, CNTs were considered as promising and application-prospective thermal management fillers due to their superior TC, tremendous mechanical strength, and large specific surface area. In general, a simple mechanical mixing between CNTs and polymeric materials was the most ordinary approach employed to manufacture thermal conductive polymer-based composites. Cui et al prepared EP/r-MWCNT composites by dispersing raw multiwalled carbon nanotubes (r-MWCNTs) in epoxy resin.…”
Section: Introductionmentioning
confidence: 99%